2012
DOI: 10.3402/tellusa.v64i0.12244
|View full text |Cite
|
Sign up to set email alerts
|

Cold air outbreaks over high-latitude sea gulfs

Abstract: A B S T R A C T Wintertime cold outbreaks were studied via a 2-D numerical model set across an 80 km wide non-frozen sea gulf along 608N ('Gulf of Finland'). In calm conditions, land breezes develop over both coasts with relatively large along-shore wind components. The mid-gulf convergence of the colliding land breezes leads to a moderate rising motion at about 600 m height, forcing bands of low cloud and snowfall along the gulf, whereas the near-surface horizontal wind shear may induce 'mini-hurricanes'. A w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…The relatively warm and wet maritime air was forced to ascend over, leading to strong convergence and vertical motion, which apparently drove the cellular convection inland. By comparing with the results of the flat-coast experiments of Savija¨rvi (2012) it can be concluded that the role of the coastal ridge was important whereas.…”
Section: Simulation Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The relatively warm and wet maritime air was forced to ascend over, leading to strong convergence and vertical motion, which apparently drove the cellular convection inland. By comparing with the results of the flat-coast experiments of Savija¨rvi (2012) it can be concluded that the role of the coastal ridge was important whereas.…”
Section: Simulation Resultsmentioning
confidence: 97%
“…He proposed that the collision of two land-breeze cells from nearby, opposing shores is the main trigger of along-shore snow bands in calm weather. In addition, Savija¨rvi (2012) suggested that this mechanism caused the snow band recorded between the Estonian and Finnish coasts in January 2006 over the Gulf of Finland, as well as the Ga¨vle snow band that hit the Swedish coast in December 1998 being caused by this mechanism. However, a full 3D numerical study of such snow bands over the Gulf of Finland has not been performed yet.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Passarelli and Braham, 1981;Savijärvi, 2012). In accordance with this relaxed definition, the American Meteorological Society (AMS) Glossary states that the land breeze 'usually' blows at night (http://amsglossary.allenpress.com/glossary).…”
Section: Are the Bands Caused By Land Breezes?mentioning
confidence: 99%